Structural Change, Fundamentals, and Growth : A Framework and Case Studies - Mc Millan, Margaret; Rodrik, Dani; Sepulveda, Claudia (World Bank, Washington, DC, 2017)
Developing countries made considerable gains during the first decade of the 21st century. Their economies grew at unprecedented rates, resulting in large reduction in extreme poverty and a significant expansion of the middle class. But more recently that progress has slowed with an economic environment of lackluster global trade, not enough jobs coupled with skills mismatches, continued globalization and technological change, greater income inequality, unprecedented population aging in richer countries, and youth bulges in the poorer ones. This essay examines how seven key countries fared from 1990-2010 in their development quest. The sample includes Brazil, India, Vietnam and four African countries -- Botswana, Ghana, Nigeria, and Zambia -- all of which experienced rapid growth in recent years, but for different reasons. The patterns of growth are analyzed in each of these countries using a unifying framework that draws a distinction between the "structural transformation" and "fundamentals" challenges in growth. Out of the seven countries, the traditional path to rapid growth of export oriented industrialization only played a significant role in Vietnam.